2020
DOI: 10.1177/1548051820980428
|View full text |Cite
|
Sign up to set email alerts
|

Exploring the Bounds of Pygmalion Effects: Congruence of Implicit Followership Theories Drives and Binds Leader Performance Expectations and Follower Work Engagement

Abstract: The topic of work engagement is moving up on the managerial agenda as it sets the stage for numerous beneficial outcomes for both organizations and their employees. It is clear, however, that not all employees are equally engaged in their job. The current study taps into theory on positive self-fulfilling prophecies induced by leaders’ high expectations of followers (i.e., the Pygmalion effect) and examines their potential to facilitate follower work engagement. By integrating literature on implicit followersh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
24
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 23 publications
(25 citation statements)
references
References 93 publications
1
24
0
Order By: Relevance
“…First, future research might include social variables (e.g., leaders' and colleagues' perception about other employees' performance) in studying the processes that influence the perception of personal productivity in remote work. Not only people's perceptions about themselves, but also about other employees, can play a fundamental role in determining one's productivity in remote work (the Pygmalion or Rosenthal effect; e.g., Veestraeten et al, 2021). Therefore, we think that including the consideration of feedback from others may help in understanding the relationship between people's overall job performance and RW productivity.…”
Section: Theoretical and Practical Implicationsmentioning
confidence: 99%
“…First, future research might include social variables (e.g., leaders' and colleagues' perception about other employees' performance) in studying the processes that influence the perception of personal productivity in remote work. Not only people's perceptions about themselves, but also about other employees, can play a fundamental role in determining one's productivity in remote work (the Pygmalion or Rosenthal effect; e.g., Veestraeten et al, 2021). Therefore, we think that including the consideration of feedback from others may help in understanding the relationship between people's overall job performance and RW productivity.…”
Section: Theoretical and Practical Implicationsmentioning
confidence: 99%
“…Instead an attribution to performance enhancement motives leads to guilt, less deviant and more organisational citizenship behaviour. Further, recent research into implicit followership theories has suggested that implicit theories can trigger a Pygmalion effect, so that individuals behave more in line with the theories others have of them, and that implicit theories might interact in predicting outcomes (Veestraeten et al ., 2020). Another recent study (Kniffin et al ., 2020) has shown that individuals differentiate between leaders and managers in terms of their implicit theories.…”
Section: Discussionmentioning
confidence: 99%
“…These perceptions that individuals hold are really their prototypes and stereotypes of how they think a leader should behave and the traits they should have (Yukl, 2013, p. 233; Da'as and Zibenberg, 2021, p. 196). Although first introduced by Eden and Leviatan in 1975, the significance of ILTs has been recognised through a considerable body of research since the 1980s (Veestraeten et al. , 2021, p. 140), as it is an area of leadership that continues to receive attention from a number of scholars (Felfe and Petersen, 2007; Popper, 2015; Ehrhart, 2012; Alabdulhadi et al.…”
Section: Implicit Theories On Leadership and Followershipmentioning
confidence: 99%